The Influence Of Work Discipline And Physical Work Environment On Employee Performance In The Tailor Department PT. Tjiwulan Putra Mandiri Tasik: - Rendiani; Karmila, Mila; Sutrisna, Arga (Jurnal Pusat Manajemen, 2024)
The purpose of this study was to determine the effect of work discipline and physical work environment on the performance of PT Tjiwulan Putra Mandiri Tasikmalaya tailor employees. The research method used is a causal associative method with a quantitative approach to 144 respondents who are employees of the tailor section. The type of data used is primary data. The data analysis technique used is multiple linear regression analysis. The results of this test prove that work discipline and physical work environment simultaneously have a significant effect on the performance of employees in the tailor section of PT Tjiwulan Putra Mandiri Tasikmalaya. Work discipline has a significant effect partially on the performance of employees in the tailor section of PT Tjiwulan Putra Mandiri Tasikmalaya. The physical work environment has a significant effect partially on the performance of employees in the tailor section of PT Tjiwulan Putra Mandiri Tasikmalaya.